2018
DOI: 10.1158/1055-9965.epi-17-0009
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with False Positive Results on Screening Mammography in a Population of Predominantly Hispanic Women

Abstract: Potential harms of screening mammography include false positive results, such as recall breast imaging or biopsies. We recruited women undergoing screening mammography at Columbia University Medical Center in New York, New York. They completed a questionnaire on breast cancer risk factors and permitted access to their medical records. Breast cancer risk status was determined using the Gail model and a family history screener. High risk was defined as a 5-year invasive breast cancer risk of ≥1.67% or eligible f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…We sought to investigate the rates of false positive mammography results in this predominantly minority, Hispanic population, as well as factors associated with higher rates of false positive results, for the reasons previously detailed. We found that among the largely Hispanic (70%) population of women presenting for screening mammography at the Avon Breast Imaging Center at CUMC and agreeing to participate in our study, approximately 53% of women had at least one false positive result on their screening mammograms over a median of 8.9 years of screening (range, 0–26) 43 . The factors associated with false positive results were similar to those of more predominantly white, non-minority populations, namely, frequency of screening and increased breast density.…”
Section: Our Observations In a Predominantly Hispanic Population Andmentioning
confidence: 75%
“…We sought to investigate the rates of false positive mammography results in this predominantly minority, Hispanic population, as well as factors associated with higher rates of false positive results, for the reasons previously detailed. We found that among the largely Hispanic (70%) population of women presenting for screening mammography at the Avon Breast Imaging Center at CUMC and agreeing to participate in our study, approximately 53% of women had at least one false positive result on their screening mammograms over a median of 8.9 years of screening (range, 0–26) 43 . The factors associated with false positive results were similar to those of more predominantly white, non-minority populations, namely, frequency of screening and increased breast density.…”
Section: Our Observations In a Predominantly Hispanic Population Andmentioning
confidence: 75%
“…27 However, these updated guidelines have not had a significant impact on changing mammography screening practices. 18,28 A recent publication found that risk-stratified breast cancer screening was cost-effective with a favorable benefit-toharm ratio using a life-table model, and there are ongoing prospective studies in the United States testing this hypothesis. 29 If systematic breast cancer risk assessment can be incorporated into clinic workflow and included in the patient's medical record (ie, incorporated into the mammography report), this may help identify women with low to average risk who may benefit from less frequent routine screening and women with high risk who may be eligible for more intensive supplemental screening (ie, breast ultrasound or magnetic resonance imaging).…”
Section: Discussionmentioning
confidence: 99%
“…We enrolled women undergoing screening mammography in the Know Your Risk: Assessment at Screening (KYRAS) survey study. 18 After providing informed consent, all participants completed a baseline self-administered questionnaire in English or Spanish. We collected information on demographics and breast cancer risk factors.…”
Section: Data Collection From Self-reported Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a prospective study called the Know Your Risk: Assessment at Screening (KYRAS) [19]. Women were approached for enrollment during routine screening mammography at the Avon Breast Imaging Center at Columbia University Irving Medical Center (CUIMC) in the Washington Heights neighborhood of New York, NY, and provided written informed consent to complete a baseline survey and to allow access to their electronic health record (EHR).…”
Section: Methodsmentioning
confidence: 99%